Translating Subtitles of Becoming Jane Film: A Pragmatic Approach - Arbain Arbain (Langkawi: Journal of The Association for Arabic and English, 2020)
Subtitling is an effective way to provide dialogues or narrative for a movie. The benefit is for people to enjoy the film even though its different from their native language. They enjoy movies over the world with different countries and styles by the dialogues translated. This research aims to know the strategy of responding to arguing in the file's subtitle titled Becoming Jane, to find out the translation techniques used by the translator, and to assess the translation quality in terms of the accuracy, acceptability, and readability. The research method is descriptive qualitative method with "Becoming Jane" movie and its subtitles as the data. Data were collected from document analysis and focus group discussions with the score of the accuracy, acceptability, and readability. The results indicate that the character used a strategy of agreeing, persisting, and complying. While six methods of translation were found, namely literal, modulation, established equivalence, borrowing, and adaptation. The quality of the translation of the strategy of responding to speech acts has been categorized as less accurate, less acceptable, and moderate in terms of readability